Alguns Impactos da Expansão da Produção de Soja no Município de Sorriso-MT - Argemiro Luís Brum (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2009)
This article aims to highlight the importance of soybean Glyceni Max and to examine the issue of economic development provided by this culture in the city of Sorriso-MT, and their impact on the progress of deforestation of the cerrado in the period 2000 to 2006. The article also highlights the lines of development of the municipality and in particular health, education, sanitation and housing. It was noted, with the data collected that the soybean crop participated with percentage between 75% and 90% of total primary municipal sector in the period studied. Also gives a percentage of the total VAT on the total taxes collected from around 75%, while the percentage of total taxes for the items of municipal development it is 80.2% and soybean participates in the total amount collected from VAT in the period, with 65%. Furthermore, the participation of soybean in relation to the total value for the lines of social development was approximately 47.46%. The percentage figures for deforestation in the municipality is 12% during the study period. This value is an indication that despite the council having an indicator of human development considered for the high standards of the Brazilian cities, there is a negative impact caused by the degradation of environmental resources.